Single-dose Antibiotic Prophylaxis in Regional Anesthesia: A Retrospective Registry Analysis. (September 2016) - Bomberg, Hagen; Krotten, Denise; Kubulus, Christine; Wagenpfeil, Stefan; Kessler, Paul; Steinfeldt, Thorsten; Standl, Thomas; Gottschalk, André; Stork, Jan; Meissner, Winfried; Birnbaum, Juergen; Koch, Thea; et al.
Abstract : Background: Catheter-related infection is a serious complication of continuous regional anesthesia. The authors tested the hypothesis that single-dose antibiotic prophylaxis is associated with a lower incidence of catheter-related infections. Methods: Our analysis was based on cases in the 25-center German Network for Regional Anesthesia database recorded between 2007 and 2014. Forty thousand three hundred sixty-two surgical patients who had continuous regional anesthesia were grouped into no antibiotic prophylaxis (n = 15, 965) and single-dose antibiotic prophylaxis (n = 24, 397). Catheter-related infections in each group were compared with chi-square test after 1:1 propensity-score matching. Odds ratios (ORs [95% CI]) were calculated with logistic regression and adjusted for imbalanced variables (standardized difference more than 0.1). Results: Propensity matching successfully paired 11, 307 patients with single-dose antibiotic prophylaxis (46% of 24, 397 patients) and with 11, 307 controls (71% of 15, 965 patients). For peripheral catheters, the incidence without antibiotics (2.4%) was greater than with antibiotic prophylaxis (1.1%, P < 0.001; adjusted OR, 2.02; 95% CI, 1.49 to 2.75, P < 0.001). Infections of epidural catheters were also more common without antibiotics (5.2%) than with antibiotics (3.1%, P < 0.001; adjusted OR, 1.94; 95% CI, 1.55 to 2.43, P < 0.001). Conclusions: Single-dose antibiotic prophylaxis was associated with fewer peripheral and epidural catheter infections. Abstract : In the German Network for Regional Anesthesia database, 11, 307 patients receiving epidural or perineural catheters and single-shot antibiotics were propensity matched with the same number of individuals who did not receive antibiotics. The adjusted odds ratio for infection, primarily defined as the presence of at least two of the symptoms redness, edema, or pressure/pain leading to catheter removal, was 2.02 (95% CI, 1.4 to 2.8) for peripheral catheters and 1.94 (95% CI, 1.6 to 2.4) for nonobstetrical epidural catheters.